The Effect of Work-Life Balance and Burnout on Trainee Job Satisfaction : Evidence from Conrad Bali - Robi Ramadhan; Ida Bagus Putu Suamba; Yulia Tri Hapsari (Cattleya Darmaya Fortuna, 2026)
The high demands of work in the hospitality industry can be a factor influencing the job satisfaction of training participants. The ability to maintain a balance between work and personal life and to manage work-related fatigue are important aspects in creating a positive training experience. Although many studies on job satisfaction have been conducted, research specifically addressing the conditions of hotel training participants remains limited. This research examines how work-life balance and exhaustion affect Conrad Bali trainees' job satisfaction. A total of 130 trainees were selected as respondents using proportional stratified random sampling in this quantitative study. IBM SPSS Statistics 25 was used to analyze structured questionnaire data using multiple linear regression. The study found that work-life balance positively impacts job satisfaction (β = 0.438; p < 0.001), whereas work exhaustion negatively impacts it (β = -0.494; p < 0.001). These two factors explain 70.2% of work satisfaction variance across training participants (R² = 0.702). Work-life balance and tiredness reduction are needed to boost intern satisfaction, according to these studies. The research findings can serve as a basis for hotel management to improve the well-being of interns and the quality of their training experience.